QLIF-08. DETERMINING THE NET CLINICAL BENEFIT IN NEURO-ONCOLOGY CLINICAL TRIALS BY COMBINING SURVIVAL AND TOXICITY DATA. Issue 11 (6th November 2017) - Sloan, Jeff; Major, Brittny; Buckner, Jan C
Abstract: Despite new treatment options for glioblastoma, the improvements in survival time have not been groundbreaking. When considering treatment options it is important for the clinician to consider both the quantity as well as the quality of life benefit of the treatment. How can a clinician incorporate efficacy and toxicity information into a single expression of comparative treatment benefit? We have devised a new quality-adjusted effect size (QASES) method that combines efficacy and toxicity information into a single expression of comparative treatment benefit. QASES is a weighted combination of the efficacy and toxicity effect sizes based on differences in efficacy and toxicity using the ½ standard deviation method Results will be presented for the four possible case combinations of significant/non-significant differences in survival and toxicity data using completed randomized clinical trials (RCT) in patients with newly diagnosed glioblastoma. As an example, a phase III RCT of radiotherapy and daily temozolomide followed by bevacizumab in adults who had centrally confirmed glioblastoma found a 3.4 months (10.7 months vs. 6.3 months) increase in PFS compared with radiotherapy and TMZ alone. When equal weights were placed on survival and toxicity, the observed Median PFS difference 3.4 months reduced to a Quality Adjusted PFS Difference of 1.2 months for anemia, 0.9 months for fatigue, -0.1 months for hypertension, 1.1 months for leukopenia and 0.5 months neutropenia. The QASES approach allows for an intuitively appealing and mathematically simple and robust approach to combining efficacy and toxicity data. Clinicians can use QASES to interpret and communicate the findings of clinical trials to patients by weighing both the efficacy and toxicity information into a single quality-adjusted estimate of efficacy.